Digitalisasi Kitab Turots: Transformasi Pesantren di Era Literasi Digital - Mukhamat Saini (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2025)
Pesantren as a traditional Islamic educational institution has an important role in maintaining and teaching Islamic knowledge, especially through the study of turots books (yellow books). However, advances in digital literacy bring challenges as well as opportunities for pesantren in adapting technology to update the learning system. The digitization of turots books is an innovative step to increase the accessibility and effectiveness of learning in the pesantren environment. This study uses a library research method with a descriptive qualitative approach to analyze the digitalization of the Turots book in the transformation of Islamic boarding schools in the era of digital literacy. Data analysis uses content analysis techniques with several stages, namely data reduction, categorization, and interpretation. The results of the study show that the digitization of turots books increases access and flexibility of learning, encourages innovation in teaching methods, and faces challenges such as limited infrastructure, teacher readiness, and resistance to change.